Release strategies of Trissolcus basalis (Scelionidae) in protected crops against Nezara viridula (Pentatomidae): Less is more. (November 2022) - Gard, Benjamin; Bout, Alexandre; Pierre, Prisca
Abstract: Nezara viridula is responsible for significant damage on cucumber, eggplant and tomato. This stink bug feeds on plant tissue causing desiccation of apices and flower bud drop; it also attacks fruits, causing deformation. Insecticides registered to control N. viridula are not compatible with natural enemies, as they disrupt integrated pest management. In a two-year trial, we evaluated the efficacy of the egg parasitoid Trissolcus basalis to control N. viridula . We tested four combinations of quantity and frequency of release of the parasitoid in the greenhouse. Each combination was repeated four times and compared to a positive control without parasitoid introduction. We observed effective control of N. viridula with the four strategies tested, but the best cost/benefit ratio was obtained with the release of 1 parasitoid/m 2 /week. The parasitism efficiency was relatively high for each strategy considered, ranging from 89 to 99%, which demonstrated a strong regulation impact on the stink bug population. Total parasitism ranged from 47 to 68%, which indicated relatively good activity and efficiency of the parasitoid, and led to a significant reduction of the damage in comparison to the control. Desiccated apices were reduced by 45 to 71% and flower bud drop by 32 to 60%. The highest damage reduction was obtained by releasing 1 parasitoid/m 2 /week. Hence, T. basalis is a good candidate for the biological control of N. viridula in protected crops. Surprisingly, the best regulation was not obtained when the highest quantity of parasitoids was released. Implications of intra-specific competition are discussed. Highlights: Trissolcus basalis effectively controlled Nezara viridula in greenhouse. Discovery efficiency ranged from 55 to 72% and parasitism efficiency from 89 to 99%. Releasing 1 parasitoid per m 2 was more efficient than 2 per m 2, if released every week. Damage was reduced by 71% for desiccated apices and by 60% for fallen flower buds.